Linguistic Research of Airport Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The linguistic research of airport terms examines the specialized vocabulary used in aviation and the specific language employed within airport environments. This field of study delves into the unique terms, jargon, and expressions used by passengers, crew members, and ground staff. It focuses on the linguistic structures, semantic nuances, and communication strategies in the airport context. Additionally, this research explores how language functions in various domains such as ticketing, security, flight announcements, and customer service, aiming to enhance communication efficiency and understanding. The study of airport terminology also reflects the intersection of language and culture, as airport terms may vary across different languages and regions, offering insight into how language evolves in a globalized context.